The green lacewings of Pakistan (Neuroptera: Chrysopidae): a faunal review with new records of genera and species - Hassan, Muhammad Asghar; Liu, Xingyue (Zootaxa, 2022)
A review of the present knowledge on the taxonomy and distribution of the green lacewings (Neuroptera: Chrysopidae) from Pakistan is presented. So far, 19 species are known to occur in Pakistan including three species newly recorded, i.e., Italochrysa aequalis (Walker, 1853), Italochrysa everetti (van der Weele, 1909), and Tumeochrysa indica Needham, 1909. In addition, there are five undetermined species of Apertochrysa Tjeder, 1966 not determined in this paper. We here describe/re-describe 16 species of the 24 Pakistani green lacewing species. Two new combinations are proposed: Apertochrysa murreensis (Tjeder, 1963) comb. nov., and Apertochrysa vartianorum (Hölzel, 1973) comb. nov. The genus Tumeochrysa Needham, 1909 is recorded for the first time in Pakistan. Identification keys are provided to all known genera and species that occur in Pakistan. Additionally, for each species, taxonomic notes, diagnosis, a complete list of synonyms, and distribution maps are provided.